2019
DOI: 10.31233/osf.io/jskct
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Late Cretaceous dinosaur remains and other tetrapod fauna from the vicinity of Tran town (Western Srednogorie)

Abstract: Brief conference report on a new Late Cretaceous tetrapod fossil site near the town of Tran (Western Srednogorie), Western Bulgaria, with notes on its dating and palaeoecology. Collected fossil material indicates presence of at least two groups of non-avian dinosaurs, crocodylomorph, and testudines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The preliminary taxonomic evaluation of the fossil assemblage at the Vrabchov dol locality indicates a rich late Santonian-early Campanian vertebrate fauna (Nikolov et al 2018), potentially one of the best found in Europe so far. Future comparisons with the Santonian vertebrate fauna of Hungary are of major interest, because they may reveal a lot about the isolated Late Cretaceous insular faunas, their composition and differences in between, and eventually elucidate the palaeobiogeography and migration history of some tetrapod groups.…”
Section: Age Of the Vrabchov Dol Locality Vs The Late Cretaceous Vert...mentioning
confidence: 97%
See 4 more Smart Citations
“…The preliminary taxonomic evaluation of the fossil assemblage at the Vrabchov dol locality indicates a rich late Santonian-early Campanian vertebrate fauna (Nikolov et al 2018), potentially one of the best found in Europe so far. Future comparisons with the Santonian vertebrate fauna of Hungary are of major interest, because they may reveal a lot about the isolated Late Cretaceous insular faunas, their composition and differences in between, and eventually elucidate the palaeobiogeography and migration history of some tetrapod groups.…”
Section: Age Of the Vrabchov Dol Locality Vs The Late Cretaceous Vert...mentioning
confidence: 97%
“…The sedimentary sequences of the formation are deposited predominantly in shallow marine palaeoenvironments, but sediments deposited in foreshore to lagoonal depositional environments also occur. The studied section has a total thickness of 8 m and is composed of grey to light grey marls, silicified marls, coal and coaly shales (Nikolov et al 2018;Text-fig. 2).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations